2020
DOI: 10.1007/s10668-020-01028-x
|View full text |Cite
|
Sign up to set email alerts
|

A global analysis on the effect of temperature, socio-economic and environmental factors on the spread and mortality rate of the COVID-19 pandemic

Abstract: We performed a global analysis with data from 149 countries to test whether temperature can explain the spatial variability of the spread rate and mortality of COVID-19 at the global scale. We performed partial correlation analysis and linear mixed effect modelling to evaluate the association of the spread rate and motility of COVID-19 with maximum, minimum, average temperatures and diurnal temperature variation (difference between daytime maximum and night-time minimum temperature) and other environmental and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Descriptive statistical results showed that COVID-19 outbreaks and related data did not meet the preconditions of Pearson correlation analysis and were mainly manifested as the non-Gaussian normal distribution, spatial autocorrelation, and possible nonlinear relations. In general, Spearman's rank correlation is an appropriate nonparametric estimator for estimating the correlation between two variables with unknown or non-Gaussian statistical distributions, and the relationship between these variables does not need to be linear ( Rahman et al, 2020 ). It is usually measured in terms of Spearman's rank correlation coefficient ρ; the formula is as follows: n is the total number of samples, and y i are the ranks of i and Y i , respectively, ρ represents the Spearman rank correlation coefficient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Descriptive statistical results showed that COVID-19 outbreaks and related data did not meet the preconditions of Pearson correlation analysis and were mainly manifested as the non-Gaussian normal distribution, spatial autocorrelation, and possible nonlinear relations. In general, Spearman's rank correlation is an appropriate nonparametric estimator for estimating the correlation between two variables with unknown or non-Gaussian statistical distributions, and the relationship between these variables does not need to be linear ( Rahman et al, 2020 ). It is usually measured in terms of Spearman's rank correlation coefficient ρ; the formula is as follows: n is the total number of samples, and y i are the ranks of i and Y i , respectively, ρ represents the Spearman rank correlation coefficient.…”
Section: Methodsmentioning
confidence: 99%
“…This coefficient varies between -1 and + 1, and the greater the absolute value of ρ, the stronger the relationship between the two variables. Like Pearson's coefficient, Spearman's absolute value of ρ in the range of 0.8-1 indicates a strong correlation, 0.6-0.8 strong correlation, 0.4-0.6 medium correlation, 0.2-0.4 weak correlation, and 0-0.2 uncorrelation ( Rahman et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The overall trends of rCFR gradually increased from 1.0% in September to 2.2% in November 2020, and stabilized at this level thereafter. We suspect that the increase trend of rCFR between September and November might associate with the decreasing air temperature during the same period in the UK, about which the evidence is found in previous studies for COVID-19 [ 50 , 51 , 52 , 53 , 54 ]. The instantaneous CFR estimates may also have the potential to monitor the mortality risk on a real-time basis, and to further examine the associations with its potential determinants, for example, pathogenic evolution, supply of critical care resources [ 55 ] and exposure to environmental factors [ 56 ].…”
Section: Resultsmentioning
confidence: 68%
“…As to the effects of climate on COVID-19 outcomes, the data are mixed, with some studies showing effects of temperature on mortality and others finding no association. [53][54][55][56] However, climate change, with its concomitant extreme weather events and particulate matter pollution, contributes to cardiopulmonary morbidity, a known risk factor for poor COVID-19 outcomes. Regardless of the nature of the interaction, because of its ubiquity, climate change is likely to affect the COVID-19 pandemic and its victims.…”
Section: Downstream (Indirect) Antibiotic Resistancementioning
confidence: 99%